2017
DOI: 10.18517/ijaseit.7.5.3452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Concentration of Tris Buffer Solution on Calcium Carbonate Precipitation in Bio-based Repair Materials

Abstract: This research examined differences in the concentration of Tris buffer solution on calcium carbonate precipitation in biobased repair materials. Four concentrations of Tris buffer solution were chosen based on previous research with initial pH 8.0 and 9.0. Initial experiments demonstrated that the concentration and pH of Tris buffer solution had an influence on the amount of precipitation of calcium carbonate. X-Ray Diffraction (XRD) analysis elucidated the morphological and structural differences of the calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Based on the result of previous experiments carried out by Putri et al [24], the highest calcium carbonate precipitates were found to the concentration of tris buffer solution in the range of 0.5 to 0.75 (mol/L) for initial pH adjusted to 9.0. The concentration of dry yeast were specified as 27 g/L, which were mixed with glucose and calcium acetate with concentrations of 0.3 mol/L and 0.15 mol/L respectively.…”
Section: Application Of Bio-based Repair Materialsmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on the result of previous experiments carried out by Putri et al [24], the highest calcium carbonate precipitates were found to the concentration of tris buffer solution in the range of 0.5 to 0.75 (mol/L) for initial pH adjusted to 9.0. The concentration of dry yeast were specified as 27 g/L, which were mixed with glucose and calcium acetate with concentrations of 0.3 mol/L and 0.15 mol/L respectively.…”
Section: Application Of Bio-based Repair Materialsmentioning
confidence: 91%
“…Based on previous research [24], amount of precipitates is mainly comprising calcium carbonate up to 48 h after they were mixed which seemed to reach about 0.388 g in the 30 ml test tube. The volume of the gap is 68.292 cm 3 and based on the calculation, required 5280.3 mL of bio-based materials to fill the leakage for 0.6 mm crack width.…”
Section: Casementioning
confidence: 92%
See 1 more Smart Citation
“…According to Kawaai [19] and Putri [30][31][32], the initial pH levels and concentration of the mixture influence the precipitation rate, particularly at the beginning of the reaction. Correspondingly, the most effective compositions in the early phases contribute to increasing the amount of precipitation, as well as speeding up the reaction rate due to the effectiveness of sealing the leakage in concrete.…”
Section: Effect Of Different Concentrations Of Yeast-based Mixtures On Calcium Carbonate Precipitationmentioning
confidence: 99%
“…Putri et al [14] also investigated the effect of dry yeast types on calcium carbonate precipitation rates in Japan. When dry yeast is selected as the microorganism, carbon dioxide, produced through microbial metabolic processes (by consuming an organic carbon source such as glucose), provides carbonate ions.…”
Section: Introductionmentioning
confidence: 99%